Activation and reactivity of epoxides on solid acid catalysts - Saikia, Lakshi; Satyarthi, J. K.; Srinivas, Darbha; Ratnasamy, P. (Journal of Catalysis, 2007)
The aminolysis of epoxides over novel solid catalysts (Bronsted-acidic SBA-15 functionalized with propylsulfonic acid and Lewis-acidic Ti-MCM-41) is reported. The acidic properties of these catalysts were determined by FTIR spectroscopy and temperature-programmed desorption of pyridine and NH3, respectively. The mesoporous solid acids of the present study are reusable and exhibit significantly higher catalytic activities than known catalysts for opening of the oxirane ring with nitrogen (aromatic and aliphatic amines)-containing and oxygen (alcohols)-containing nucleophiles. A range of beta-amino, alcohols with high regioselectivity and stereoselectivity were synthesized. Adsorption studies as well as the sigmoid shape of the conversion- versus-time plots show that the epoxide and amine compete for adsorption on the acidic sites (-SO3H or Ti4+) on the catalyst surface. Epoxide adsorption and activation on acid sites are the more critical processes. Catalytic activity decreases with increasing basicity of the amines and/or the alcohol, as well as the dielectric constant of the solvent. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: aminolysis and alcoholysis of epoxides; beta-Amino alcohols; ring opening of epoxides; SBA-15 functionalized with propylsulfortic acid; Solid acids; Ti-MCM-41

Comparative catalytic activity of Mn(Salen) complexes grafted on SBA-15 functionalized with amine, thiol and sulfonic acid groups for selective aerial oxidation of limonene - Salkia, Lakshi; Srinivas, Darbha; Ratnasamy, Paul (Microporous and Mesoporous Materials, 2007)
SBA-15 molecular sieves were functionalized with propylamine, propylthiol and propylsulfonic acid groups. Mn(Salen)Cl complexes were grafted on these organo-functionalized SBA-15. The support and the type of organo-functional group influenced the electronic structure (oxidation state and redox behavior) and chemo selectivity of the Mn-complexes in the oxidation of limonene. The Mn ions were reduced from +3 to +2, the extent of this reduction on different supports decreasing in the order: SBA- 15-pr-SH > SBA- 15-prSO(3)H > SBA-15-pr-NH2- Mn(Salen)Cl supported on propylthiol-functionalized SBA-15 yielded the 1,2-limonene epoxide with 100% chemo- and regioselectivity. Higher electron density at the site of Mn ions and the consequent lower redox potential of the Mn-complexes on immobilization are the probable causes for their efficient and selective catalytic activity. Solvents, additives (N-MeIm) and co-reagents (iso-butyraldehyde), which facilitated formation of Mn2+ ions, enhance the catalytic activity. A part of the Mn complexes was leached out of the solid phase during the reaction and the extent of this with different catalysts decreased in the order: SBA-l5-pr-NH2-Mn(Salen)Cl > SBA- 15-pr-SO3H-Mn(Salen)Cl > SBA- 15-pr-SH-Mn(Salen)Cl. (C) 2007 Elsevier Inc. All rights reserved

Regio- and stereoselective synthesis of beta-amino alcohols over titanosilicate molecular sieves - Satyarthi, Jitendra K.; Saikia, Lakshi; Srinivas, Darbha; Ratnasamy, P. (Applied Catalysis A-General, 2007)
A novel application of titanosilicate molecular sieves in the synthesis of P-amino alcohols via aminolysis of epoxides, at mild and solvent-free conditions, is reported, for the first time. A range of beta-amino alcohols with nearly 100% regio- and stereoselectivity was produced over these reusable solid catalysts in high yields. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Aminolysis of epoxides; synthesis of beta-amino alcohols; Ti-MCM-41; titanosilicate molecular sieves

Active sites in vanadia/titania catalysts for selective aerial oxidation of beta-picoline to nicotinic acid - Srinivas, Darbha; Hoelderich, Wolfgang F.; Kujath, Steffen; Valkenberg, Michael H.; Raja, Thirumalaiswamy; Saikia, Lakshi; Hinze, Ramona; Ramaswamy, Veda (Journal of Catalysis, 2008)
Vanadia/titania catalysts with varying vanadium content were prepared by impregnation using three different titania carrier materials of varying surface area, The structure of active vanadium species for beta-picoline oxidation was investigated. Vanadium is mainly in the +5 oxidation state as revealed by electron paramagnetic resonance (EPR) and V-51 magic-angle spinning nuclear magnetic resonance (V-51 MAS NMR) spectroscopy techniques. Diffuse reflectance UV-visible (DRUV-vis) spectroscopy and spectral deconvolution enabled identification of at least five different types of vanadium oxide species in these catalysts: monomeric tetrahedral VO43-, polymeric distorted tetrahedral VO3-, square pyramidal V2O5, octahedral V2O62- and V4+ oxide species. While both VO43- and VO3- species are active in beta-picoline oxidation, the latter having a distorted tetrahedral geometry yielded the desired products-picolinaldehyde and nicotinic acid. High surface area, anatase structure for the support and dispersed, distorted tetrahedral vanadium oxide species are the key parameters determining the activity and selectivity of these oxidation catalysts. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Active vanadium species; Nicotinic acid; Oxidation of beta-picoline; Selective aerial oxidation; Spectroscopic investigations; Vanadia/titania

Double metal cyanides as efficient solid acid catalysts for synthesis of beta-amino alcohols under solvent-free conditions - Saikia, Lakshi; Satyarthi, J. K.; Gonnade, Rajesh G.; Srinivas, Darbha; Ratnasamy, P. (Catalysis Letters, 2008)
A novel application of Fe-Zn double metal cyanide complexes as solid, acid catalysts for regioselective synthesis of beta-amino alcohols under solvent-free conditions via ring-opening of epoxides with amines is reported for the first time. The conversion of epoxides to beta-amino alcohols is nearly 100%. In the reaction with styrene oxide, regioselective beta-amino alcohol formation is higher with aromatic than with aliphatic amines. Strong Lewis acidic Zn(2+) ions in the catalyst are probably the active sites in this reaction.
Keywords: beta-Amino alcohols; double metal cyanide (DMC); regioselective ring-opening of epoxides; Single crystal x-ray structure; solid Lewis-acid catalyst

Functionalized SBA-15 and its catalytic applications in selective organic transformations - Srinivas, Darbha; Saikia, Lakshi (Catalysis Surveys from Asia, 2008)
Ordered, mesoporous SBA-15 functionalized with organic and inorganic moieties exhibits efficient catalytic activity in a variety of organic transformations. In this account, reviewing our own work, three-sets of surface-modified SBA-15 materials have been investigated. The first-set of materials consists of SBA-15 modified with organo-acidic (propyl thiol and propyl sulfonic acid) and basic (propyl amine and propyl adenine) moieties. The second-set of materials was prepared by grafting Mn complexes to the organo-functionalized SBA-15. The third-set composes of nanocrystalline metal oxides supported on SBA-15. All these catalysts have been characterized by structural and spectroscopic techniques. Catalytic activities of the first-set of solid materials have been investigated in acid/base-catalyzed reactions viz., ring-opening of epoxides with amines (producing beta-amino alcohols), esterification, three-component-Mannich reactions and cycloaddition of CO(2) to epoxides. The Mn complexes grafted on organofunctionalized SBA-15 are efficient catalysts for the chemo-, regio- and stereoselective aerial oxidation of monoterpenes at ambient conditions. TiO(x), VO(x), MoO(x) and WO(x) supported on SBA-15 catalyzed biomimetic oxyhalogenation of aromatic compounds. In all these reactions, the functionalized SBA-15 showed high selectivity.
Keywords: grafted Mn-Salen complexes; Ordered mesoporous silica; organofunctionalized SBA-15; oxidation catalysts; Oxyhalogenation of aromatics

Magnetic phase transition in valence tautomers as polymorphs of 3-iodolawsone: Single crystal X-ray structure, DSC and EPR studies - Zaware, Santosh B.; Dagade-Waghmode, Shobha; Gonnade, Rajesh G.; Srinivas, Darbha; Rane, Sandhya Y. (Journal of Molecular Structure, 2009)
Three polymorphs of 3-iodolawsone (I-III) have been isolated and characterized by single crystal X-ray diffraction, electron paramagnetic resonance (EPR) spectroscopy and differential scanning calorimetry (DSC) techniques. Polymorphs I and II were crystallized from methanol in two different valence tautomeric forms: hydroxynaphthoquinone (HNQ) and hydroxynaphthoseimquinone (HNSQ) as needles and thick plates, respectively. Polymorph III was crystallized from ethanol in HNQ form, as thin plates Chiral crystals of I belongs to the orthorhombic P2(1)2(1)2(1) space group: II and III belong to the monochnic non-centrosymmetric space group Cc. The molecules are packed via O-H O bonding and pi . pi stacking interactions. The study reveals that relatively stronger intermolecular H-bonding (2.02 angstrom) and most favoured pi . pi stacking (similar to 3 49 angstrom) interactions lead II to HNSQ radicals, presence of which was confirmed by EPR (g = 2.0052) spectroscopy. Interestingly, these materials exhibit crystal-to-crystal magnetic phase transition from polymorph I (diamagnetic) to polymorph II (paramagnetic structure) at 171.1 degrees C as identified by DSC and X-ray crystallographic studies (C) 2009 Elsevier B.V. All rights reserved
Keywords: 3-Iodolawsone; Hydroxynaphthoquinone (HNQ); Hydroxynaphthosemiquinone radical (HNSQ); Magnetic phase transition; Polymorphs; Valence tautomers

Selective oxidations over zeolite- and mesoporous silica-based catalysts: selected examples - Ratnasamy, Paul; Srinivas, Darbha (Catalysis Today, 2009)
Selective oxidation of hydrocarbons/terpenes in the liquid phase are reported over three categories of zeolite- and mesoporous silica-based catalysts: (1) transition metal complexes (metal phthalocyanines, copper acetate dimers and Co/Mn acetate trimer) encapsulated in zeolite-Y, (2) transition metal complexes (Mn-Salen), grafted on SBA-15, and (3) transition metal ions in framework positions of zeolites and mesoporous molecular sieves like Ti-silicates. Upon heterogenization, the metal complexes exhibited enhanced catalytic acitivity/selectivity. The causes for the enhanced catalytic activity/product selectivity have been explored. Dimer formation (copper acetate) or geometric distortion in the zeolite cavities (metal phthalocyanines) and consequent changes in energy levels and redox potentials are shown to modify the catalytic activity (in the selective oxidation of hydrocarbons) of the encapsulated metal complexes. In the case of Mn-Salen grafted on SBA-15, increasing the acidity of the siliceous surface (by -SO(3)H groups, for example) leads to a more facile reduction of the Mn ions and, thereby, enhanced catalytic activity in the selective epoxidation of limonene. When Ti ions are introduced in framework positions, reactive metal-oxo species are formed on contact with H(2)O(2) or O(2), Which influence the mode of O-O cleavage (heterolytic/homolytic) and product selectivity. The structure-function relationships in these catalysts are reported. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Mn-Salen; Oxidation of hydrocarbons and limonene; Reactive oxo species; Selective oxidation; Titanosilicates; Zeolite-encapsulated metal complexes

Synthesis of framework Ti-substituted, 3-D hexagonal, mesoporous Ti-SBA-12 for selective catalytic oxidation - Kumar, Anuj; Srinivas, Darbha; Ratnasamy, Paul (Chemical Communications, 2009)
Framework Ti-substituted, 3-D hexagonal mesoporous, Ti-SBA-12, obtained for the first time by direct hydrothermal synthesis, oxidises bulky molecules such as cyclohexene and cyclooctene to the epoxides with >96% selectivity at high conversion levels (>60%).

Influence of surface hydrophobicity on the esterification of fatty acids over solid catalysts - Satyarthi, Jitendra K.; Srinivas, Darbha; Ratnasamy, Paul (Energy & Fuels, 2010)
The relative roles of surface acidity and hydrophobicity in the methylation of fatty acids (C(8) - C(18)) to the corresponding methyl esters were investigated over three solid acid catalysts: Fe-Zn double-metal cyanide (DMC), sulfated zirconia (SZ), and Al-MCM-41. The esterification reaction was faster and the apparent activation energy was lower over SZ and Al-MCM-41 than on DMC because of their higher acid strength, specific surface area, and pore diameter. Over SZ and Al-MCM-41, the apparent activation energy for esterification increased with the chain length of the fatty acid. A reverse trend, however, was observed over DMC. The relative adsorption of methanol and fatty acids (compared to water) was higher on DMC than on SZ and Al-MCM-41. Hence, in addition to the acidic and textural properties, surface hydrophobicity and relative surface coverage by reactants/products also play an important role in reactions of long-chain fatty acids with alcohols on solid catalysts.

Regiospecific oxyhalogenation of aromatics over SBA-15-supported nanoparticle group IV-VI metal oxides - Saikia, Lakshi; Rajesh, M.; Srinivas, Darbha; Ratnasamy, P. (Catalysis Letters, 2010)
TiO(x), VO(x), MoO(x) and WO(x) supported on SBA-15 exhibit efficient catalytic activity for oxyhalogenation of aromatics with the H(2)O(2)-halide ion system. Unlike the hitherto known solid catalysts, these reusable catalysts yield the para-halogenated product with 100% selectivity at 298 K and moderate acidic pH (3-5). The catalytic activity was enhanced by five orders of magnitude when supported on SBA-15.
Keywords: Haloperoxidase activity; Ordered mesoporous silica; Oxyhalogenation of aromatics; SBA-15; Supported metal oxides

Antioxidant and anticancer activities of supramolecularly controlled magnetostructural halo-oximes of lawsone - Zaware, Santosh B.; Gonnade, Rajesh G.; Srinivas, Darbha; Khan, Ayesha A.; Rane, Sandhya Y. (New Journal of Chemistry, 2011)
Crystal engineering based on halogen bonding together with host-guest interactions of water molecules via H-bonding, stabilizing supramolecular architecture in chloro 1, bromo 2 and iodo 3 oximes of lawsone, is discussed. 1 and 2 crystallize in orthorhombic, non-centrosymmetric space group Pna2(1) while 3 crystallizes in monoclinic P2(1)/n space group. Non-covalent competitive interactions of asymmetric solvation and halogen bonding can have a large influence on the spin distribution in 1, 2 and 3 derivatives of spin carrier lawsone live polymer as revealed by single crystal X-ray and EPR studies. The significant C3-Cl/Br center dot center dot center dot O, C3-Cl/Br center dot center dot center dot H, O-H center dot center dot center dot O-C, C-H center dot center dot center dot pi and pi center dot center dot center dot pi interactions have been identified in the molecular assemblies leading to net magnetostructures of halo-oximes. Dimer-of-dimer-type tetrameric radical assembly of 3 and interacting bi- and monoradical chain on 2(1) axis in 1 and 2 have been identified. The proton-coupled electron transfers possibly govern the antioxidant nature in halooximes of spin carrier lawsone in terms of oxygen reduction to water molecules. Such activity is found to be directly proportional to the spin (radical) concentrations in 1 to 3 and increases in order 1 < 2 < 3 according to halogen bonding effect. The antioxidant chemical DPPH assays for scavenging of such free radicals result in similar trend of increasing order like 1 < 2 < 3, but the chemical in vitro as well as ex vivo SOD antioxidant activities and biological anticancer activity on MCF-7, Hela and HL-60 cell lines show the increasing order 3 < 2 < 1 according to H-bonding effect. This probably could be attributed to the conversion of superoxide radical ions into H(2)O(2), which leads to greater oxidative stress leading to apoptosis.

Azide derivatized anticancer agents of vitamin K-3: X-ray structural, DSC, resonance spectral and API studies - Badave, Kirti D.; Patil, Yogesh; Gonnade, Rajesh G.; Srinivas, Darbha; Dasgupta, Rajan; Khan, Ayesha A.; Rane, Sandhya (Journal of Molecular Structure, 2011)
Compound 1 [1-imino (acetyl hydrazino)-Vitamin K-3], displays valence tautomerically related electronic isomers as Form land Form II. Form I exhibits 2D packing fragment with 1D ribbon chains of N-H center dot center dot center dot O hydrogen bonds and shows EPR silent features. While Form II is EPR active and exhibits biradical nature with double quantum transitions at g = 2.0040. H-1 NMR of compound 2, [1-imino (hydrazino carboxylate)-Vitamin K-3] and Form II exhibit pi delocalization via resonance assisted H-bonding [RAHB] effect compared to Form I. Molecular interactions in Form I and II are visualized by DSC. The electronic structures of compounds 1 and 2 have been correlated to their API values by measuring anticancer activities, mitochondrial potentials and DNA shearing patterns. Form II and compound 2 indicate mitochondria mediated apoptosis (similar to 75% cell death) while Form I causes 35% cell death. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Anticancer agents; API (Active Pharmaceutical Ingredients); Electronic isomers; RAHB (resonance assisted H-bonding); Vitamin K-3

Biodiesel production from vegetable oils and animal fat over solid acid double-metal cyanide catalysts - Srinivas, Darbha; Satyarthi, Jitendra K. (Catalysis Surveys from Asia, 2011)
Biodiesel comprises of fatty acid alkyl esters prepared from vegetable oils or animal fat by esterification/transesterification with short-chain alcohols (methanol or ethanol, for example). It is a biodegradable renewable fuel. Its production is growing exponentially due to greater concerns about environmental protection and depletion of fossil fuel resources. Further, its production from non-edible oils and animal fat is more desirable than from edible oils due to lower cost of non-edible feedstocks and elimination of food verses fuel issues. Solid acid catalysts are ideal for conversion of such low-grade oils to biodiesel. Biodiesel from non-edible oils can be produced by two methods: (1) simultaneous esterification of fatty acids and transesterification of fatty acid glycerides and (2) hydrolysis of glycerides followed by esterification. This account reports the catalytic performance of solid, Fe-Zn double-metal cyanide (DMC) complexes and other acid catalysts in these transformations for biodiesel production. The factors influencing the catalytic performance of the solid acid catalysts in biodiesel production are discussed.
Keywords: Biodiesel; Double-metal cyanide; Esterification; Hydrolysis; solid acid catalysts; transesterification

Factors Influencing the Kinetics of Esterification of Fatty Acids over Solid Acid Catalysts - Satyarthi, Jitendra Kumar; Radhakrishnan, Sambhu; Srinivas, Darbha (Energy & Fuels, 2011)
The kinetics of esterification of fatty acids with alcohols over three different solid acid catalysts, viz., large pore zeolite-beta (H beta), micro-mesoporous Fe-Zn double-metal cyanide (DMC), and mesoporous Al-MCM-41, have been reported. Hydrophobicity of these catalysts increases in the order: Al-MCM-41 < H beta < DMC. The chain lengths of the fatty acid (C(8.0)-C(18.1)) and alcohol (C(1)-C(8)) molecules have been varied, and their influence on kinetic parameters has been studied. The present study reveals that porosity and surface hydrophobicity of the catalyst are the two important factors other than acid properties (concentration and strength of acid centers) that influence the esterification reaction.

Fourier transform infrared spectroscopic method for monitoring hydroprocessing of vegetable oils to produce hydrocarbon-based biofuel - Satyarthi, Jitendra K.; Srinivas, Darbha (Energy & Fuels, 2011)
A novel Fourier transform infrared spectroscopic method is reported, for the first time, to estimate the conversion of vegetable oil (soybean oil, for example) to hydrocarbon-based biofuel via hydroprocessing. The infrared peak attributed to the carboxyl group (O-C=O) is used as a marker to determine the conversion of fatty acid glycerides in soybean oil to hydrocarbons. Unlike the conventional gas chromatographic method, this new method of estimation is fast and requires no derivatization of the sample and predetermination of response factors of each chemical component in vegetable oil/product samples. H-1 and C-13 nuclear magnetic resonance spectroscopy techniques are also reported to substantiate and confirm the purity and product formation in the hydroprocessing reaction.

Novel application of a Fe-Zn double-metal cyanide catalyst in the synthesis of biodegradable, hyperbranched polymers - Sebastian, Joby; Srinivas, Darbha (Chemical Communications, 2011)
The use of Fe-Zn double-metal cyanide as a solid catalyst for synthesizing biodegradable, hyperbranched polymers from diacids and glycerol has been reported, for the first time, wherein acidity, micro-mesoporosity and hydrophobicity of the catalyst played an important role in controlling gelation.

Aminolysis of epoxides catalyzed by three-dimensional, mesoporous titanosilicates, Ti-SBA-12 and Ti-SBA-16 - Kumar, Anuj; Srinivas, Darbha (Journal of Catalysis, 2012)
The application of three-dimensional, mesoporous titanosilicates (Ti-SBA-12 and Ti-SBA-16) as reusable, solid catalysts for the synthesis of a range of beta-amino alcohols in high yields and selectivity through ring-opening of epoxides with amines at ambient and solvent-free conditions is reported, for the first time. These mesoporous titanosilicates (Si/Ti = 20-80) were prepared by a direct hydrothermal synthesis route adjusting the concentration of HCl (0.05-2 M) used in the synthesis. Ti ions in these catalysts were mostly substituted for Si in the framework. Water adsorption and Si-29 magic-angle spin nuclear magnetic resonance spectroscopy revealed that Ti-SBA-16 is more hydrophobic than Ti-SBA-12. Mesoporosity, three-dimensional architecture, surface hydrophobicity and easy access of Lewis acidic, framework-substituted Ti sites are the factors responsible for the superior activity of Ti-SBA-16 compared to Ti-SBA-12 and the hitherto known solid catalysts for this reaction. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Aminolysis of epoxides; beta-Amino alcohol; Mesoporous titanosilicates; Molecular sieves; Ring opening of epoxides with amines; Ti-SBA-12; Ti-SBA-16

Challenges and opportunities in biofuels production - Srinivas, Darbha; Satyarthi, Jitendra Kumar (Indian Journal of Chemistry Section A-Inorganic Bio-Inorganic Physical Theoretical & Analytical Chemistry, 2012)
Biofuels are attractive alternative to petroleum diesel. They are renewable, non-toxic, biodegradable, carbon neutral and lead to reduced tailpipe emissions. This article presents the current state-of-art processes of their production and discusses the opportunities and future challenges in this area of research.
Keywords: Biodiesel; biofuels; Deoxygenation; Hydrotreatment; Renewable fuels; Solid catalysts; Transesterification (fatty acid glycerides); Vegetable oils/fats

Selective oxidation of cyclic olefins over framework Ti-substituted, three-dimensional, mesoporous Ti-SBA-12 and Ti-SBA-16 molecular sieves - Kumar, Anuj; Srinivas, Darbha (Catalysis Today, 2012)
Framework Ti-substituted, three-dimensional, mesoporous titanosilicates, Ti-SBA-12 and Ti-SBA-16, were prepared by direct hydrothermal synthesis method. These catalysts showed catalytic activity higher than the hitherto known titanosilicates for the oxidation of cyclic olefins (cyclohexene and cyclooctene) with tert.-butyl hydroperoxide. An epoxide selectivity of 100% and olefin conversion greater than 92% were obtained. Cubic Ti-SBA-16 with interconnected cage-like mesopore structure was more active than hexagonal Ti-SBA-12. X-ray diffraction and diffuse reflectance UV-vis, Fourier transform infrared, Raman and electron paramagnetic resonance spectroscopies provided evidence for the substitution of Ti4+ (for Si4+) in the framework locations. The catalytic activity correlated with the concentration of framework-substituted, tetrahedral Ti4+ ions. Easy accessibility of the active sites and the three-dimensional mesoporous structure are the possible causes for the superior activity of these titanosilicate catalysts. (C) 2012 Elsevier B. V. All rights reserved.
Keywords: Epoxidation of cyclic olefins; mesoporous materials; Molecular sieves; Selective oxidation; Ti-SBA-12; Ti-SBA-16; Titanosilicates

Catalytic activity of ZIF-8 in the synthesis of styrene carbonate from CO2 and styrene oxide - Zhu, Minqi; Srinivas, Darbha; Bhogeswararao, Seemala; Ratnasamy, Paul; Carreon, Moises A. (Catalysis Communications, 2013)
The catalytic activity of ZIF-8 in the synthesis of styrene carbonate from carbon dioxide and styrene oxide is presented. ZIF-8 crystals displayed catalytic activity even at temperatures as low as 50 degrees C, with styrene carbonate yields as high as similar to 54% at 100 degrees C. In contrast to many prior-art catalysts, solvents or co-catalysts were not required. Pyridine and ammonia were used as probe molecules to estimate the type and density of acid sites in fresh and reused ZIF-8 catalysts. DRIFT spectroscopy of adsorbed pyridine revealed the presence of both Bronsted (B) and Lewis (L) acid sites. The B-sites have nearly vanished in the case of recycled ZIF-8 catalysts. The simultaneous presence of both the acid sites and the nitrogen basic moieties from the imidazole linker in ZIF-8 promoted the adsorption of the CO2 on the solid surface and its further conversion to the cyclic carbonate. The ZIF-8 catalysts could be recycled and reused without significant loss in catalytic activity. Published by Elsevier B.V.
Keywords: CO2 conversion; cyclic carbonates; Styrene carbonate; Zeolitic imidazolate frameworks; ZIF-8

Direct synthesis of amides from amines using mesoporous Mn-SBA-12 and Mn-SBA-16 catalysts - Kumar, Anuj; Nepak, Devadutta; Srinivas, Darbha (Catalysis Communications, 2013)
Manganese incorporated SBA-12 and SBA-16 catalyze the tandem reaction of aliphatic primary amine, aerial oxygen and ammonia solution at moderate conditions producing amide in yields as high as 50 mol%. The Mn-SBA-12 and Mn-SBA-16 catalysts with Si/Mn output molar ratio in the range 230 to 748 were prepared by the direct hydrothermal synthesis method and characterized. Weak acidity and Mn in +3 oxidation state are the key factors enable the synthesis of product amide in high yields. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Aerial oxidation; Amide synthesis; Benzyl amine; Manganese incorporated SBA-12 and SBA-16; Mesoporous Mn-silica catalyst

Efficient, direct synthesis of dimethyl carbonate from CO2 using a solid, calcined zirconium phenylphosphonate phosphite catalyst - Unnikrishnan, Pulikkeel; Varhadi, Poonam; Srinivas, Darbha (RSC Advances, 2013)
Direct synthesis of dimethyl carbonate (DMC) from CO2 and methanol with 100 mol% selectivity using a solid, reusable, hydrophobic, calcined zirconium phenylphosphonate phosphite catalyst is reported for the first time. DMC yield as high as 26 mmol g(-1) catalyst correlated with the concentration of acid and base sites is obtained.

Hydroxylation of phenol with hydrogen peroxide catalyzed by Ti-SBA-12 and Ti-SBA-16 - Kumar, Anuj; Srinivas, Darbha (Journal of Molecular Catalysis A-Chemical, 2013)
We report here, for the first time, the application of ordered, three-dimensional, mesoporous titanosilicates, Ti-SBA-12 and Ti-SBA-16, as reusable solid catalysts, for hydroxylation of phenol, an industrially important organic transformation. The reactions were conducted using 30% aqueous H2O2 as oxidant. The catalysts of this work are more efficient than the hitherto known mesoporous Ti-silicates. They are more para-product selective than TS-1 and other titanosilicates. Ti-SBA-12 exhibited higher activity and hydroquinone/catechol selectivity (by nearly two times) than Ti-SBA-16. H2O2 efficiency of similar to 90 mol% was obtained. Our study reveals that framework substituted Ti with pseudo-tetrahedral geometry, three-dimensional mesoporosity as well as surface structure are the unique features responsible for the high catalytic activity and selectivity of these titanosilicate catalysts. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Catalytic liquid-phase hydroxylation of phenol; Molecular sieves; Ordered mesoporous titanosilicates; Oxidation with hydrogen peroxide; Ti-SBA-12; Ti-SBA-16

Influence of method of preparation of solid, double-metal cyanide complexes on their catalytic activity for synthesis of hyperbranched polymers - Sebastian, Joby; Srinivas, Darbha (Applied Catalysis A-General, 2013)
Catalytic activity of a series of Fe-Zn double-metal cyanide (DMC) complexes with varying structural and acidic properties has been investigated for the synthesis of hyperbranched polyesters (HPs) from glycerol and succinic acid/adipic acid. The DMC complexes were prepared using different complexing and co-complexing agents. Hydrophobicity of the surface, Lewis acidity and micro-mesoporous architecture are the critical features of DMC enabled control on gelation process in preparing HPs of high degree of branching. The micro-mesoporous architecture of DMC acts as a nano-reactor for reactant molecules to form primary condensation products which further polymerize yielding dendrimers. Hyperbranched polyesters of degree of branching as high as 90% could be achieved without gelation using DMC catalysts. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Dendrimers; Double-metal cyanide; heterogeneous catalysis; Hydrophobic solid acid catalyst; Hyperbranched polymers

Cu(II) conjugation along the transformation of a vitamin K-3 derivative to a dinaphthoquinone methide radical - Badave, Kirti D.; Patil, Shalaka S.; Khan, Ayesha A.; Srinivas, Darbha; Butcher, Raymond J.; Gonnade, Rajesh G.; Puranik, Vedavati G.; Pinjari, Rahul V.; Gejji, Shridhar P.; Rane, Sandhya Y. (New Journal of Chemistry, 2014)
1,1'-Methide-bi-vitamin K-3 (B) has been isolated as a dinaphthoquinone methide radical (DNQM) by the transformation of 1-imino(acetylhydrazino)-vitamin K-3 (A). The transformation follows a biomimetic activation pathway mediated via Cu(II) ion catalyzed oxidative coupling. Single crystal X-ray and electron spin resonance (ESR) experiments combined with density functional calculations elucidate the ``resonance structure'' of the DNQM radical (B). Fluorescence investigations reveal that DNQM facilitates interaction with the cysteine residue. As compared to the parent substrate, B shows a depletion in the level of GSH, triggering apoptosis in HeLa cells.

Effects of method of preparation on catalytic activity of Co-Zn double-metal cyanide catalysts for copolymerization of CO2 and epoxide - Sebastian, Joby; Srinivas, Darbha (Applied Catalysis A-General, 2014)
Co-Zn double-metal cyanide (DMC) complexes are well-known catalysts for ring-opening polymerization of epoxides and co-polymerization of CO2 and epoxides. This work provides an insight on structure-activity relationship of DMC for poly(cyclohexene carbonate) synthesis. Seven samples of DMC were prepared by different methods and mode of reagent addition. Highly active catalyst could be synthesized even without using a co-complexing agent. CO2 adsorption studies revealed that higher the guest-host interaction higher would be the catalytic activity. High density and strength of Lewis acid sites, moderate crystallinity, low crystal symmetry (rhombohedral/monoclinic), Cl- ions and coordinated tert.-butanol (complexing agent) control the catalytic activity for polycarbonates. Chloride in the structure avoided induction period by increasing acidity of the catalyst and thereby, improving the guest-host interactions. Polycarbonates with CO2 incorporation as high as 86 mol%, average molecular weight of 20900 and polydispersity index of 1.8 were prepared at complete conversion of cyclohexene oxide. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Carbon dioxide; CO2 utilization; Copolymerization of CO2 and cyclohexene oxide; Double-metal cyanide; Polycarbonate; Structure-activity relationship

Effect of alkali and alkaline earth metal ions on benzyl alcohol oxidation activity of titanate nanotube-supported Au catalysts - Nepak, Devadutta; Srinivas, Darbha (RSC Advances, 2015)
Sodium titanate nanotubes (NaTNTs) were prepared by alkali treatment of anatase titania. They were then ion-exchanged with alkali and alkaline earth metal ions to get ATNTs (A = Li+, K+, Cs+, Mg2+, Ca2+, Sr2+ and Ba2+). Gold (1-5 wt%) was supported on these nanotubes by a deposition-precipitation method and investigated as a catalyst for the selective oxidation of benzyl alcohol with air/molecular oxygen (1 atm) under solvent-and alkali-free conditions. Detailed characterization by X-ray powder diffraction, high resolution transmission electron microscopy, N-2-physisorption, diffuse reflectance UV-visible spectroscopy, X-ray photoelectron spectroscopy and CO2-temperature-programmed desorption techniques revealed that the basicity of the catalyst influences the uptake, mean particle size, electronic properties and oxidation activity of the supported gold. Benzaldehyde formed with a selectivity of about 99%. The catalytic activity (turnover frequency) was found to have a direct relationship with the basicity and an inverse relationship with the Au particle size. Among the catalysts investigated, Au/BaTNTs, having higher basicity, smaller Au particles and higher metal dispersion, showed enhanced catalytic activity than the other Au/ATNT catalysts. Pd addition to Au leading to Au-Pd/BaTNTs increased the activity (TOF) but lowered the selectivity for benzaldehyde (80 wt%). Titanate nanotubes donate electron density to Au particles, yielding electron rich Au ions, which are responsible for activating molecular oxygen and oxidizing benzyl alcohol. Au/BaTNTs, having higher basicity and lower size Au nanoparticles than the other Au/ATNT, activates molecular oxygen more easily and thereby enhances the catalytic activity.

Factors influencing catalytic activity of Co-Zn double-metal cyanide complexes for alternating polymerization of epoxides and CO2 - Sebastian, Joby; Srinivas, Darbha (Applied Catalysis A-General, 2015)
Co-Zn double-metal cyanides (DMCs) show good catalytic activity towards copolymerization of epoxides and CO2. A deep insight into the structural aspects of the catalysts that control their catalytic performance is addressed in this work. Method of preparation of DMC catalysts was found to have influence on their structure, which in turn dictated their catalytic activity. Complexing agent (t-BuOH) and density of strong acid sites of DMC catalysts were found critical factors responsible for their activity. Selectivity of DMC towards polycarbonates depends on the amount of alkali ion content in their composition. Induction period of the catalysts was governed by the strength of acid sites and by the presence of dispersed ZnCl2 in the composition. This study provides an understanding of the prime features of DMC catalysts that can be tuned for high productivity of polycarbonates. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: CO2 utilization; Copolymerization of epoxides and CO2; Double-metal cyanide; Polycarbonate

Effects of thermal treatment of ZnO-ZnCr2O4 catalyst on the particle size and product selectivity in dehydrocyclization of crude glycerol and ethylenediamine - Sarkari, Reema; Krishna, Vankudoth; Sudhakar, Medak; Rao, Tumula Venkateshwar; Padmasri, Aytam Hari; Srinivas, Darbha; Venugopal, Akula (Kinetics and Catalysis, 2016)
The ZnO-ZnCr2O4 (Zn-Cr-O) sample obtained by decomposition of Zn-Cr hydrotalcite precursor was subjected to the thermal treatment at different temperatures and the physico-chemical properties of the Zn-Cr-O system were compared with its catalytic behavior in dehydrocyclization of crude glycerol and ethylenediamine (EDA). Upon high temperature treatment of Zn-Cr-O the Cr6+ ions underwent autoreduction to form stable Cr3+ species and the particle size of both ZnO and ZnCr2O4 increased dramatically. Thermal effect did not influence the intermolecular cyclisation of EDA to form pyrazine. By contrast, an inversely proportional dependence was found between the rate of formation of 2-methylpyrazine and the particle size of Zn-Cr-O whereas the rate of 2-pyrazinylmethanol was directly proportional to the particle size.

Spectroscopy and catalytic activity study of gold supported on barium titanate nanotubes for styrene epoxidation - Nepak, Devadutta; Srinivas, Darbha (Applied Catalysis A-General, 2016)
Gold (0.5-5 wt.%) supported on barium titanate nanotubes (Au/BaTNT) were prepared, characterized and for the first time, investigated as catalysts for selective oxidation of styrene with oxygen (O-2 or H-2 + O-2) and peroxides (H2O2 or TBHP). Conversion of styrene enhanced when H-2 was co-added to O-2 in the reactions. Au/BaTNT activated O-2 and H-2 and produced H2O2 in situ for use in oxidations. Peroxides were found better oxidants than O-2. At optimized conditions, styrene oxide selectivity of 80.1 wt.% at styrene conversion of 60.5 wt.% was achieved over Au(1 wt.%)/BaTNT using TBHP. Au particles (5.0-7.4 nm) were dispersed and decorated on the walls of BaTNT. They exhibited superior performance to the known Au catalysts in styrene oxidation. Reactive oxygen species formed during oxidation reactions were followed with in situ spectral characterizations (diffuse reflectance UV-vis and FT -Raman). Au/BaTNT was reusable in four recycles with little loss in catalytic activity. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Au Nanoparticles; reactive oxygen species; spectroscopy; Styrene Oxidation; Titanate nanotubes

Selective and reusable Pt-WO x /Al 2 O 3 catalyst for deoxygenation of fatty acids and their esters to diesel-range hydrocarbons - Janampelli, Sagar; Srinivas, Darbha (Catalysis Today, 2017)
Tungsten oxide promoted platinum catalysts (Pt-WOx/Al2O3) of varying composition were prepared by wet impregnation method and reduced in hydrogen atmosphere. X-ray powder diffraction and photoelectron spectroscopy revealed that Pt is completely reduced to metallic state while tungsten is in +6 and +5 oxidation state. Pt crystallite and particle sizes increased (from 1.2 to 1.4 nm and 2.5 to 3 nm, respectively) in presence of WOx (CO-chemisorption and transmission electron microscopy). Tungsten addition augmented strong acid sites. It enhanced significantly the catalytic activity of Pt/Al2O3 in deoxygenation of fatty acids and their methyl esters. Tungsten altered the reaction pathway from decarbonylation/decarboxylation to hydrodeoxygenation. A catalyst with 4 wt% Pt and 8 wt% W exhibited high catalytic performance. Complete conversion of oleic acid and octadecane product selectivity in the range 67.1 − 80.8% was obtained. Pt-WOx/Al2O3 is a stable and reusable fatty acid deoxygenation catalyst.
Keywords: biofuels; Deoxygenation; Diesel-range hydrocarbons; Fatty acids; Pt catalyst

Modern trends in inorganic chemistry: celebration of inorganic chemistry in India - Chikkali, Samir H.; Anand, Venkataramanarao G.; Srinivas, Darbha; Kumbhar, Avinash S. (Journal of Chemical Sciences, 2018)